Evaluation of clinician’s input in surgical pathology process in a developing country (Journal of Pathology of Nepal, 2020)
Background: The clinician's role is paramount in surgical pathologist’s evaluation of surgical specimens. The study aims at evaluating clinicians’ role in the surgical pathology process in Nigeria.Materials and Methods: This is a three-year (2016-2018) study of all (1262) routines surgical pathology specimens (SPS) received at the histopathology department of Delta State University Teaching Hospital Oghara. Parameters analyzed include the quality of the containers and fixatives used during specimen submission and the information supplied by the clinician (Specimen nature, patients’ age, gender, address, , hospital number, phone number and clinical information. The information was analyzed using Microsoft Excel 2017 and the result presented in tables.Results: Nine (0.6%) SPS were not stored in appropriate fixative while in 88(8.3%) cases, the quantity of fixatives were inadequate. Forty (3.2%) of sample containers were inadequate while 86(6.8%) of the sample labels were wrongly placed. Fifty-two containers accommodated more than one SPS. The gender, age, address, hospital number, time of collection in day and hour were omitted in 21(1.7%), 18(1.4%), 627(49.7%), 921(73.0%) and 58(4.6%) of the cases respectively. The clinical request form, clinical findings, previous investigations, previous treatment history and presumptive or definitive diagnosis were missing in 288(22.8%), 192(15.2%), 282(22.4%), 424(33.6%), 340(27.0%) and 98(7.7%) cases respectively. Their names, contact telephone numbers and signature were omitted in the request in 58(4.6%), 1230(97.5%) and 143(11.3%) of the cases respectively.Conclusions: Among the parameters evaluated, Clinicians are mostly non-compliant in providing clinical information and their phone numbers. Continuous education and interaction with clinicians, computerized information management system and introduction of non-conformity registrar are possible ways of closing this gap.